Influencing the Misinformed Misbehaver: An Analysis of Public Policy towards Uncertainty and External Effects - Francesca Barigozzi; Bertrand Villeneuve (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
We study a situation where the government influences consumers` behavior by providing both information and incentives. More generally, we propose a methodology for solving models of signl cum cheap talk. We develop the case of consumption choice in the presence of uncertainty nd external effects. The institutions used by delivering biased information to the misbehaver. We study the equilibrium trade-off between informing and giving incentives. Environmental tax policy, anti-smoking campaigns and policy against antibiotics over-consumption serve as illustration.
Keywords: 330